A mesh adaptation for non-stationary problems - Felcman, Jiří; Kubera, Petr (Proceedings in applied mathematics and mechanics, 2007)
The subject‐matter of this paper is the numerical simulation of the multidimensional inviscid compressible transonic gas flow. An adaptive mesh is constructed in the framework of the ADER higher order cell‐centred finite volume scheme. An adaptation strategy based on the residual error indicator is followed by a recovery of the approximate solution on the new mesh. (© 2008 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)